ҒӘРЕЗСИЗЛИК ЖЫЛЛАРЫНДА ҚАРАҚАЛПАҚСТАНДА МЕКТЕПКЕ ШЕКЕМГИ ТӘЛИМНИҢ РАӮАЖЛАНЫӮЫНЫҢ МЕТОДОЛОГИЯЛЫҚ ТИЙКАРЛАРЫ - Машерипова, А. (SCIENCE and SOCIETY, 2021)
The article provides a number of information on the development of preschool education and preschool education system in Karakalpakstan today. The state of the pre-school education is based on sources about the enrollment of preschool children in pre-school education institutions and the activities of the organizations.